Laser Applications as a Preventive Measure Treatment for Those with Periodontitis: Randomized Clinical Trail - Ismail, Hussam; Rasol Jalaawi, Wissam; Imad Albaheli, Bahil; Albaheli BI, Ismail H Jalaawi W (Journal of Neonatal Surgery, 2025)
Background: Mechanical debridement is the best option when treating periodontitis. Nevertheless, it has been suggested that the use of lasers as an adjunct may lead to better treatment outcome. long-term gingival disease leads to destruction of periodontal tissues. Diode lasers have shown potential effect in both therapeutic and preventive applications. Objective: Evaluate the effect of diode lasers as assistant to scaling and root planning (SRP) Methods: Forty patients with stage III periodontitis were enrolled in a randomized controlled clinical trial and randomly assigned to receive SRP alone (control group) and combined SRP with diode laser (980 nm) (test group) with beam parameters: 400 lm fiber diameter, 1.5 W average power, and 10 s/pulse duration. Pocket depth (PD), bleeding on probing (BOP), and relative attachment level (RAL) were measured at baseline and after six weeks recall visit. Results: By the end of the trial, both groups evaluated clinical indices had improved relative to the baseline, with notable distinctions between groups. Conclusion: When treating stage lll periodontitis with laser therapy in addition to SRP is considered to be viable treatment option.